O trevo fractal como modelo de referência no projeto de produtos em pequenas empresas - Alves, Alexandre de Castro (2009)
Product Development Process happens in a particular way at each company, due to its size, culture, technological characteristics and market, through technics, skills and Knowledge Management. For decision taking and risks minimization of this process companies use reference models at the products development. However, these models show a systematic size, with stages and actions, and a subjective size, related to human skill, such as creative process and knowledge transformation. In These companies those reference models must fit to some specific characteristics, such as: management focused on the entrepreneur; dificulty of getting data for decisions; rationality and few formalization of controls; simple and low cost structures. In this context, it is a challenge to find a reference model with systemic form that fits to micro and small companies. These companies must be more competitive, and developing products using a reference model apropriated to their characteristics is necessary in order to minimize risks. In the reference models of the bibliography were identified the main stages of the project and its context at mico and small companies, important to the conception process, for concepts and solution creation. However, this research ranges the development initial stages, since the ideas untill the conception and prototype making, for test and approvation. The greater investment for product development is in these stages, as the later stages are more technical, and outsourcing is possible. Creativity Model Fractal Clover is assessed at the initial stages of the product in micro and small companies and their actions can be applied as a formal and simplified reference model. For this, as a methodological procedure it was executed a qualitative exploratory research with case studies and action researches in four small companies. These companies are an intentional sample as strategy and procedure in the product development, compounded by offensive, opportune and imitative strategies, with formal and informal procedures. To assess the profiles of these small companies, two generated a new product concept for offensive strategy, one developed a new product generation for opportunist strategy and other a new family of product for imitative strategy. In this work, it was verified that stages and actions of the Fractal Clover Model were according to their characteristics. In this way, the model can be applied at formalization of stages and actions in the development, after being done, or as support in the development, as reference model during the product project. Clover Fractal application in these companies made possible the formalization and organization of the information, resulting in knowledge for products and the next projects.